Microscale Hardness of Acidic Electroless Ni-P/Ni-P-SiC Nano Composite Depositions - Ram, Munna; Ansari, Moh. Abdul Aleem; Sharma, Awanish Kumar; Sharma, Sulaxna; Choudhary, Vipin (Journal of Graphic Era University, 2023)
T<span dir="ltr" style="left: calc(var(–scale-factor)*78.26px); top: calc(var(–scale-factor)*382.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00289);" role="presentation">he EL<span dir="ltr" style="left: calc(var(–scale-factor)*104.30px); top: calc(var(–scale-factor)*382.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.06052);" role="presentation">Ni-<span dir="ltr" style="left: calc(var(–scale-factor)*117.50px); top: calc(var(–scale-factor)*382.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00646);" role="presentation">P along with <span dir="ltr" style="left: calc(var(–scale-factor)*176.66px); top: calc(var(–scale-factor)*382.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.06052);" role="presentation">Ni-P-<span dir="ltr" style="left: calc(var(–scale-factor)*199.01px); top: calc(var(–scale-factor)*382.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.929823);" role="presentation">SiC<span dir="ltr" style="left: calc(var(–scale-factor)*214.01px); top: calc(var(–scale-factor)*382.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.874197);" role="presentation">nano-<span dir="ltr" style="left: calc(var(–scale-factor)*236.69px); top: calc(var(–scale-factor)*382.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.905614);" role="presentation">composite <span dir="ltr" style="left: calc(var(–scale-factor)*282.41px); top: calc(var(–scale-factor)*382.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.8964);" role="presentation">coatings <span dir="ltr" style="left: calc(var(–scale-factor)*320.35px); top: calc(var(–scale-factor)*382.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.88805);" role="presentation">were <span dir="ltr" style="left: calc(var(–scale-factor)*344.11px); top: calc(var(–scale-factor)*382.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.95202);" role="presentation">plated on <span dir="ltr" style="left: calc(var(–scale-factor)*387.79px); top: calc(var(–scale-factor)*382.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.966239);" role="presentation">mild steel (AISI1040) substrates <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*395.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.96913);" role="presentation">effectively<span dir="ltr" style="left: calc(var(–scale-factor)*114.62px); top: calc(var(–scale-factor)*395.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.976256);" role="presentation">. The <span dir="ltr" style="left: calc(var(–scale-factor)*140.90px); top: calc(var(–scale-factor)*395.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.971582);" role="presentation">ultrafine SiC <span dir="ltr" style="left: calc(var(–scale-factor)*197.81px); top: calc(var(–scale-factor)*395.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.963475);" role="presentation">particles with <span dir="ltr" style="left: calc(var(–scale-factor)*257.33px); top: calc(var(–scale-factor)*395.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.874197);" role="presentation">nano-<span dir="ltr" style="left: calc(var(–scale-factor)*280.13px); top: calc(var(–scale-factor)*395.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.872836);" role="presentation">size <span dir="ltr" style="left: calc(var(–scale-factor)*299.69px); top: calc(var(–scale-factor)*395.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.946146);" role="presentation">range of <span dir="ltr" style="left: calc(var(–scale-factor)*338.35px); top: calc(var(–scale-factor)*395.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.904332);" role="presentation">50-<span dir="ltr" style="left: calc(var(–scale-factor)*351.67px); top: calc(var(–scale-factor)*395.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.95128);" role="presentation">70 nm as <span dir="ltr" style="left: calc(var(–scale-factor)*394.75px); top: calc(var(–scale-factor)*395.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.860802);" role="presentation">second <span dir="ltr" style="left: calc(var(–scale-factor)*426.55px); top: calc(var(–scale-factor)*395.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.83526);" role="presentation">phase<span dir="ltr" style="left: calc(var(–scale-factor)*449.26px); top: calc(var(–scale-factor)*395.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.932463);" role="presentation">particles were <span dir="ltr" style="left: calc(var(–scale-factor)*510.70px); top: calc(var(–scale-factor)*395.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.895441);" role="presentation">co- <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*408.53px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.904944);" role="presentation">incerted <span dir="ltr" style="left: calc(var(–scale-factor)*107.90px); top: calc(var(–scale-factor)*408.53px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.96065);" role="presentation">into<span dir="ltr" style="left: calc(var(–scale-factor)*123.38px); top: calc(var(–scale-factor)*408.53px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.860264);" role="presentation">an <span dir="ltr" style="left: calc(var(–scale-factor)*136.58px); top: calc(var(–scale-factor)*408.53px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.936929);" role="presentation">acidic <span dir="ltr" style="left: calc(var(–scale-factor)*164.18px); top: calc(var(–scale-factor)*408.53px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.885124);" role="presentation">electroless <span dir="ltr" style="left: calc(var(–scale-factor)*210.05px); top: calc(var(–scale-factor)*408.53px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.06052);" role="presentation">Ni-<span dir="ltr" style="left: calc(var(–scale-factor)*223.37px); top: calc(var(–scale-factor)*408.53px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.9213);" role="presentation">P bath. <span dir="ltr" style="left: calc(var(–scale-factor)*256.13px); top: calc(var(–scale-factor)*408.53px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.942357);" role="presentation">The SiC nano-<span dir="ltr" style="left: calc(var(–scale-factor)*316.99px); top: calc(var(–scale-factor)*408.53px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.912485);" role="presentation">particles <span dir="ltr" style="left: calc(var(–scale-factor)*354.55px); top: calc(var(–scale-factor)*408.53px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.962293);" role="presentation">of 4 gpl concentration were used for co- <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*421.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.945456);" role="presentation">deposition into <span dir="ltr" style="left: calc(var(–scale-factor)*136.58px); top: calc(var(–scale-factor)*421.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.848578);" role="presentation">an <span dir="ltr" style="left: calc(var(–scale-factor)*149.66px); top: calc(var(–scale-factor)*421.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.05817);" role="presentation">EL Ni-<span dir="ltr" style="left: calc(var(–scale-factor)*178.70px); top: calc(var(–scale-factor)*421.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.932727);" role="presentation">P bath. The sodium hypophosphite <span dir="ltr" style="left: calc(var(–scale-factor)*326.23px); top: calc(var(–scale-factor)*421.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.95712);" role="presentation">particularly <span dir="ltr" style="left: calc(var(–scale-factor)*375.91px); top: calc(var(–scale-factor)*421.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.902259);" role="presentation">is selected as <span dir="ltr" style="left: calc(var(–scale-factor)*434.11px); top: calc(var(–scale-factor)*421.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.904659);" role="presentation">a reducer <span dir="ltr" style="left: calc(var(–scale-factor)*476.02px); top: calc(var(–scale-factor)*421.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.948819);" role="presentation">in chemical <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*434.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.890782);" role="presentation">reactions. <span dir="ltr" style="left: calc(var(–scale-factor)*113.54px); top: calc(var(–scale-factor)*434.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.995527);" role="presentation">After <span dir="ltr" style="left: calc(var(–scale-factor)*137.42px); top: calc(var(–scale-factor)*434.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.942702);" role="presentation">two hours completion of <span dir="ltr" style="left: calc(var(–scale-factor)*239.57px); top: calc(var(–scale-factor)*434.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922888);" role="presentation">platings, <span dir="ltr" style="left: calc(var(–scale-factor)*276.65px); top: calc(var(–scale-factor)*434.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.881658);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*291.77px); top: calc(var(–scale-factor)*434.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.801776);" role="presentation">as-<span dir="ltr" style="left: calc(var(–scale-factor)*303.41px); top: calc(var(–scale-factor)*434.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.875121);" role="presentation">coated <span dir="ltr" style="left: calc(var(–scale-factor)*332.59px); top: calc(var(–scale-factor)*434.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00091);" role="presentation">EL <span dir="ltr" style="left: calc(var(–scale-factor)*347.59px); top: calc(var(–scale-factor)*434.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.06052);" role="presentation">Ni-<span dir="ltr" style="left: calc(var(–scale-factor)*360.91px); top: calc(var(–scale-factor)*434.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.893586);" role="presentation">P/<span dir="ltr" style="left: calc(var(–scale-factor)*369.31px); top: calc(var(–scale-factor)*434.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.06052);" role="presentation">Ni-P-<span dir="ltr" style="left: calc(var(–scale-factor)*391.51px); top: calc(var(–scale-factor)*434.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.93701);" role="presentation">SiC <span dir="ltr" style="left: calc(var(–scale-factor)*409.39px); top: calc(var(–scale-factor)*434.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.0076);" role="presentation">pl<span dir="ltr" style="left: calc(var(–scale-factor)*417.19px); top: calc(var(–scale-factor)*434.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.898948);" role="presentation">atings <span dir="ltr" style="left: calc(var(–scale-factor)*444.10px); top: calc(var(–scale-factor)*434.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.888231);" role="presentation">were heat treated <span dir="ltr" style="left: calc(var(–scale-factor)*515.98px); top: calc(var(–scale-factor)*434.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.881964);" role="presentation">at <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*448.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.904332);" role="presentation">400<span dir="ltr" style="left: calc(var(–scale-factor)*90.74px); top: calc(var(–scale-factor)*448.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.940306);" role="presentation">C in argon <span dir="ltr" style="left: calc(var(–scale-factor)*137.06px); top: calc(var(–scale-factor)*448.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.0296);" role="presentation">(Ar) <span dir="ltr" style="left: calc(var(–scale-factor)*157.34px); top: calc(var(–scale-factor)*448.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.918784);" role="presentation">environment <span dir="ltr" style="left: calc(var(–scale-factor)*210.89px); top: calc(var(–scale-factor)*448.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.996);" role="presentation">for <span dir="ltr" style="left: calc(var(–scale-factor)*225.65px); top: calc(var(–scale-factor)*448.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.909782);" role="presentation">lone <span dir="ltr" style="left: calc(var(–scale-factor)*245.93px); top: calc(var(–scale-factor)*448.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.864758);" role="presentation">one h<span dir="ltr" style="left: calc(var(–scale-factor)*268.37px); top: calc(var(–scale-factor)*448.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.9213);" role="presentation">our <span dir="ltr" style="left: calc(var(–scale-factor)*284.81px); top: calc(var(–scale-factor)*448.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.924061);" role="presentation">period. <span dir="ltr" style="left: calc(var(–scale-factor)*316.03px); top: calc(var(–scale-factor)*448.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921477);" role="presentation">As coating time increases thickness of coating also <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*462.31px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.858447);" role="presentation">increases. <span dir="ltr" style="left: calc(var(–scale-factor)*113.54px); top: calc(var(–scale-factor)*462.31px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.915553);" role="presentation">The thickness of coating for all samples is found in between of range 20 to 25 micrometer. <span dir="ltr" style="left: calc(var(–scale-factor)*479.14px); top: calc(var(–scale-factor)*462.31px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.904637);" role="presentation">Further the <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*475.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.953051);" role="presentation">micro-<span dir="ltr" style="left: calc(var(–scale-factor)*98.66px); top: calc(var(–scale-factor)*475.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.899638);" role="presentation">structure <span dir="ltr" style="left: calc(var(–scale-factor)*136.10px); top: calc(var(–scale-factor)*475.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.950253);" role="presentation">along with <span dir="ltr" style="left: calc(var(–scale-factor)*181.34px); top: calc(var(–scale-factor)*475.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.972172);" role="presentation">micro-<span dir="ltr" style="left: calc(var(–scale-factor)*208.01px); top: calc(var(–scale-factor)*475.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.878722);" role="presentation">hardness of <span dir="ltr" style="left: calc(var(–scale-factor)*256.37px); top: calc(var(–scale-factor)*475.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.79035);" role="presentation">as-<span dir="ltr" style="left: calc(var(–scale-factor)*268.01px); top: calc(var(–scale-factor)*475.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.878316);" role="presentation">deposited and heated coupons <span dir="ltr" style="left: calc(var(–scale-factor)*390.31px); top: calc(var(–scale-factor)*475.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.869552);" role="presentation">and <span dir="ltr" style="left: calc(var(–scale-factor)*407.47px); top: calc(var(–scale-factor)*475.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.893586);" role="presentation">were <span dir="ltr" style="left: calc(var(–scale-factor)*429.31px); top: calc(var(–scale-factor)*475.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.907567);" role="presentation">investigated <span dir="ltr" style="left: calc(var(–scale-factor)*480.34px); top: calc(var(–scale-factor)*475.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.996);" role="presentation">for <span dir="ltr" style="left: calc(var(–scale-factor)*494.50px); top: calc(var(–scale-factor)*475.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.880455);" role="presentation">surface <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*488.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.942768);" role="presentation">morphology by FE<span dir="ltr" style="left: calc(var(–scale-factor)*148.46px); top: calc(var(–scale-factor)*488.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.948923);" role="presentation">SEM <span dir="ltr" style="left: calc(var(–scale-factor)*171.98px); top: calc(var(–scale-factor)*488.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.96687);" role="presentation">and EDAX <span dir="ltr" style="left: calc(var(–scale-factor)*220.01px); top: calc(var(–scale-factor)*488.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919676);" role="presentation">respectively. <span dir="ltr" style="left: calc(var(–scale-factor)*273.89px); top: calc(var(–scale-factor)*488.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.907776);" role="presentation">The <span dir="ltr" style="left: calc(var(–scale-factor)*292.49px); top: calc(var(–scale-factor)*488.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.934738);" role="presentation">randomly <span dir="ltr" style="left: calc(var(–scale-factor)*333.67px); top: calc(var(–scale-factor)*488.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.890303);" role="presentation">dispersal <span dir="ltr" style="left: calc(var(–scale-factor)*372.19px); top: calc(var(–scale-factor)*488.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.934001);" role="presentation">of SiC nano-<span dir="ltr" style="left: calc(var(–scale-factor)*424.27px); top: calc(var(–scale-factor)*488.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.958822);" role="presentation">particles into the EL Ni- P-<span dir="ltr" style="left: calc(var(–scale-factor)*81.02px); top: calc(var(–scale-factor)*501.91px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.957071);" role="presentation">matrix <span dir="ltr" style="left: calc(var(–scale-factor)*110.42px); top: calc(var(–scale-factor)*501.91px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.923967);" role="presentation">is <span dir="ltr" style="left: calc(var(–scale-factor)*120.62px); top: calc(var(–scale-factor)*501.91px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.953799);" role="presentation">shown for <span dir="ltr" style="left: calc(var(–scale-factor)*165.38px); top: calc(var(–scale-factor)*501.91px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.978346);" role="presentation">4gpl by micro-<span dir="ltr" style="left: calc(var(–scale-factor)*226.73px); top: calc(var(–scale-factor)*501.91px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921041);" role="presentation">structural results<span dir="ltr" style="left: calc(var(–scale-factor)*294.05px); top: calc(var(–scale-factor)*501.91px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.11825);" role="presentation">. I<span dir="ltr" style="left: calc(var(–scale-factor)*303.53px); top: calc(var(–scale-factor)*501.91px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.944616);" role="presentation">nsertion of <span dir="ltr" style="left: calc(var(–scale-factor)*351.07px); top: calc(var(–scale-factor)*501.91px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.951762);" role="presentation">ultrafine SiC particles <span dir="ltr" style="left: calc(var(–scale-factor)*444.22px); top: calc(var(–scale-factor)*501.91px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.02775);" role="presentation">into Ni-<span dir="ltr" style="left: calc(var(–scale-factor)*476.50px); top: calc(var(–scale-factor)*501.91px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.993248);" role="presentation">P matrix, it <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*515.11px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.885054);" role="presentation">appears that <span dir="ltr" style="left: calc(var(–scale-factor)*124.70px); top: calc(var(–scale-factor)*515.11px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.95241);" role="presentation">size of <span dir="ltr" style="left: calc(var(–scale-factor)*155.66px); top: calc(var(–scale-factor)*515.11px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.04592);" role="presentation">Ni/<span dir="ltr" style="left: calc(var(–scale-factor)*168.38px); top: calc(var(–scale-factor)*515.11px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.06052);" role="presentation">Ni-P <span dir="ltr" style="left: calc(var(–scale-factor)*190.85px); top: calc(var(–scale-factor)*515.11px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.92079);" role="presentation">grainthroughout <span dir="ltr" style="left: calc(var(–scale-factor)*258.77px); top: calc(var(–scale-factor)*515.11px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.914685);" role="presentation">plating process <span dir="ltr" style="left: calc(var(–scale-factor)*323.71px); top: calc(var(–scale-factor)*515.11px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.877587);" role="presentation">reduced <span dir="ltr" style="left: calc(var(–scale-factor)*358.99px); top: calc(var(–scale-factor)*515.11px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.86296);" role="presentation">and <span dir="ltr" style="left: calc(var(–scale-factor)*376.99px); top: calc(var(–scale-factor)*515.11px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.928288);" role="presentation">introverted <span dir="ltr" style="left: calc(var(–scale-factor)*424.39px); top: calc(var(–scale-factor)*515.11px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.950829);" role="presentation">the grain growth <span dir="ltr" style="left: calc(var(–scale-factor)*496.06px); top: calc(var(–scale-factor)*515.11px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.966384);" role="presentation">for the <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*528.43px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.978531);" role="presentation">period of <span dir="ltr" style="left: calc(var(–scale-factor)*113.90px); top: calc(var(–scale-factor)*528.43px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.946234);" role="presentation">the heat treatment. The micro-<span dir="ltr" style="left: calc(var(–scale-factor)*241.13px); top: calc(var(–scale-factor)*528.43px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.93754);" role="presentation">hardness at HV30 <span dir="ltr" style="left: calc(var(–scale-factor)*316.15px); top: calc(var(–scale-factor)*528.43px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.93269);" role="presentation">scale was improved <span dir="ltr" style="left: calc(var(–scale-factor)*401.83px); top: calc(var(–scale-factor)*528.43px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.972203);" role="presentation">significantly <span dir="ltr" style="left: calc(var(–scale-factor)*455.86px); top: calc(var(–scale-factor)*528.43px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.962863);" role="presentation">by <span dir="ltr" style="left: calc(var(–scale-factor)*469.78px); top: calc(var(–scale-factor)*528.43px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.941147);" role="presentation">adding up <span dir="ltr" style="left: calc(var(–scale-factor)*515.02px); top: calc(var(–scale-factor)*528.43px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00439);" role="presentation">of <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*542.35px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922573);" role="presentation">especially SiC nano-<span dir="ltr" style="left: calc(var(–scale-factor)*155.90px); top: calc(var(–scale-factor)*542.35px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.962083);" role="presentation">particles into acidic Ni-<span dir="ltr" style="left: calc(var(–scale-factor)*252.05px); top: calc(var(–scale-factor)*542.35px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.905395);" role="presentation">P elect<span dir="ltr" style="left: calc(var(–scale-factor)*279.65px); top: calc(var(–scale-factor)*542.35px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.900472);" role="presentation">roless bath after heated <span dir="ltr" style="left: calc(var(–scale-factor)*377.23px); top: calc(var(–scale-factor)*542.35px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.865357);" role="presentation">at <span dir="ltr" style="left: calc(var(–scale-factor)*387.55px); top: calc(var(–scale-factor)*542.35px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.906137);" role="presentation">400 <span dir="ltr" style="left: calc(var(–scale-factor)*409.39px); top: calc(var(–scale-factor)*542.35px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.986312);" role="presentation">C for <span dir="ltr" style="left: calc(var(–scale-factor)*433.87px); top: calc(var(–scale-factor)*542.35px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.980344);" role="presentation">time of <span dir="ltr" style="left: calc(var(–scale-factor)*466.30px); top: calc(var(–scale-factor)*542.35px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927634);" role="presentation">one hour. The <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*555.67px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.924778);" role="presentation">increment in <span dir="ltr" style="left: calc(var(–scale-factor)*124.70px); top: calc(var(–scale-factor)*555.67px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.85236);" role="presentation">hardness <span dir="ltr" style="left: calc(var(–scale-factor)*162.14px); top: calc(var(–scale-factor)*555.67px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.01837);" role="presentation">of Ni-P-<span dir="ltr" style="left: calc(var(–scale-factor)*195.29px); top: calc(var(–scale-factor)*555.67px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.93701);" role="presentation">SiC <span dir="ltr" style="left: calc(var(–scale-factor)*212.81px); top: calc(var(–scale-factor)*555.67px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.874197);" role="presentation">nano-<span dir="ltr" style="left: calc(var(–scale-factor)*235.49px); top: calc(var(–scale-factor)*555.67px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.90314);" role="presentation">composite coatings <span dir="ltr" style="left: calc(var(–scale-factor)*315.19px); top: calc(var(–scale-factor)*555.67px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.918416);" role="presentation">against Ni-<span dir="ltr" style="left: calc(var(–scale-factor)*359.23px); top: calc(var(–scale-factor)*555.67px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.902228);" role="presentation">P coating <span dir="ltr" style="left: calc(var(–scale-factor)*399.19px); top: calc(var(–scale-factor)*555.67px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.937819);" role="presentation">is <span dir="ltr" style="left: calc(var(–scale-factor)*408.43px); top: calc(var(–scale-factor)*555.67px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.909574);" role="presentation">explained